THE APPLICATION OF TIME TOKEN MODEL USING PHOTO STORY TO IMPROVE STORY TELLING ABILITY FOR THE FOURTH GRADE STUDENT OF ELEMENTARY SCHOOLS - Utami, Khotimatunnisa (KALAM CENDEKIA PGSD KEBUMEN, 2016)
The objectives of this research are: (1) to describe the steps on the application of Time Token model using photo story media, (2) to improve story telling ability through the application of Time Token model using photo story media for the IV B class in SDN 2 Kebadongan in the academic year of 2015/2016. This research is a collaborative Classroom Action Research (CAR) conducted within three cycles. Each cycle consisted of two meetings including planning, action, observation, and reflection. Subjects of the research were IV B class students of SD Negeri 2 Kebadongan totaling 20 students. The conclusion of this research is the application of Time Token using photo story media can improve story telling ability for IV B class students in SD Negeri 2 Kebadongan in the academic year of 2015/2016 through ten steps as follow (1) the steps of Time Token model using photo story media consisted of ten stages, namely: (a) opening, (b) deliver objectives of learning, (c) explain materials of text in photo story media, (d) group division, (e) give assignment, and (f) give coupon, (g) students tell story, (h) give score, (i) conclude the materials, (j) evaluation. (2) the application of Time Token using photo story media can improve story telling ability for IV B class students in SD Negeri 2 Kebadongan in the academic year of 2015/2016.Keywords: time token, photo story, story telling ability